2012
DOI: 10.1016/j.febslet.2012.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Pro42 and Val45 of staphylokinase modulate intermolecular interactions of His43–Tyr44 pair and specificity of staphylokinase–plasmin activator complex

Abstract: Edited by Richard CogdellKeywords: Staphylokinase Plasminogen activation Molecular modeling Site-directed mutagenesis Enzyme-substrate complex Protein-protein interaction a b s t r a c t Staphylokinase (SAK) forms a 1:1 stoichiometric complex with plasmin (Pm) and changes its substrate specificity to create a plasminogen (Pg) activator complex. The His 43 -Tyr 44 pair of SAK resides within the active site cleft of the partner Pm and generates intermolecular contacts to confer Pg activator ability to the SAK-Pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 32 publications
6
20
0
Order By: Relevance
“…Pg activation assay for SAK and SAKVEK was performed in 96‐well microtiter plates as we have described previously [22, 23]. Briefly, SAK or SAKVEK (5 nM) was mixed with Pg (1.5 μM) in a tris assay buffer (50 mM Tris‐HCl, pH 7.5, containing 0.1% BSA, 100 mM NaCl, and 0.01% Tween 80) with 1 mM chromozyme in a microtiter plate, and generation of plasmin was measured by absorbance at 405 nm at 25 °C in a BioTEK Power wave X micro plate reader (VT, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pg activation assay for SAK and SAKVEK was performed in 96‐well microtiter plates as we have described previously [22, 23]. Briefly, SAK or SAKVEK (5 nM) was mixed with Pg (1.5 μM) in a tris assay buffer (50 mM Tris‐HCl, pH 7.5, containing 0.1% BSA, 100 mM NaCl, and 0.01% Tween 80) with 1 mM chromozyme in a microtiter plate, and generation of plasmin was measured by absorbance at 405 nm at 25 °C in a BioTEK Power wave X micro plate reader (VT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Fibrin clot lysis assay was performed as described previously [22]. Briefly, fibrinogen (2 mg/mL) was mixed with 500 nM Pg and 1 mM CaCl 2 in HEPES buffer (pH 7.5) containing 100 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Pg‐activation profile of PadA was generated by mixing 75 n M of PadA with 1.5 µM BPg in HEPES buffer (10 mM HEPES pH 7.5, 0.1% BSA, and 0.01% Tween 80, with or without 100 mM NaCl) containing 1 mM chromozyme in a 96 wells microtiter plate and generation of Pm was measured as a function of time at 405 nm at 25°C in a BioTEK Power wave X microplate reader . To examine the effect of various effectors on Pg activation, the activation profiles of PadA:BPg complex were generated with increasing concentration of Cl − ions, fibrinogen, and CNBr digested fibrinogen.…”
Section: Methodsmentioning
confidence: 99%
“…Only a few studies have been conducted to understand staphylokinase at the molecular level. The results identified that the residues 26, 42–50, 65–69, and 75 are important for the plasmin “partner” binding [[263], [264], [265], [266], [267]], while the residues 11–16, 46–50, 65–69, and 97–98 are involved in the binding and the processing of the plasminogen “substrate” [256,266,[268], [269], [270]]. In contrast, the first ten N-terminal residues are not required for the activity and are cleaved by active plasmin [268,[271], [272], [273], [274], [275]].…”
Section: Staphylokinasementioning
confidence: 99%